The master of arts in applied linguistics graduates’ perceptions on the program and their competencies - Rowanne Marie Maxilom Mangompit; Cindy Alcisto-Augusto (Journal of Education and Learning (EduLearn), 2022)
This study determined and analyzed the graduates’ evaluation of the master of arts in applied linguistics program on their perspectives on the contribution of the program to the present work demands, competencies in their work to further advance career and program enhancement. This study used the quantitative-qualitative research methods by using the modified self-administered questionnaires based on Schomburg primarily and interviews. The data revealed that the graduates perceived the relevance, appropriateness, and satisfaction of their program to their work. The graduates were also trained in terms of writing and presenting reports, critical thinking, managing their time and publishing. However, the program needed to enhance the skills in publication which could be attributed to the lack of internal motivation to publish one’s research output and availability of journals for publication. Thus, this study implies that there is a need to strengthen the research agenda of the department. It is indeed recommended that the students should be required by faculty members to submit their final papers for review and publication to a selected journal and publishing the master’s theses before and after earning the master of arts in applied linguistics (MAAL) program should be encouraged, reinforced, and practiced. A scholarly journal could also be created.